2019
DOI: 10.5871/jba/007s1.167
|View full text |Cite
|
Sign up to set email alerts
|

‘For the English to see’ or effective change? How supply chains are shaped by laws and regulations, and what that means for the exposure of modern slavery

Abstract: Global supply chains cross and connect judicial systems, providing regulatory and legal frameworks in which supply chains operate. This article investigates the impact and implementation of modern slavery laws and the broader legal framework surrounding Brazilian-UK beef and timber supply chains towards their modern slavery exposure in connection with their supply-chain characteristics. The article outlines the current challenges presented by modern slavery, labour exploitation, and human rights implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…This represents worker exploitation, which is a characteristic of modern slavery (Parker and Chung, 2018). In addition, reports surface from time to time of factory suicides and physical abuse of workers by managers and supervisors, which is also consistent with a form of modern slavery (Stevenson and Cole, 2018;Christ et al, 2019;Landman and Silverman, 2019;Mende, 2019;Pinheiro et al, 2019;Voss et al, 2019;Flynn and Walker, 2020). This paper examines 'how' power/distance and uncertainty avoidance aspects of Chinese culture affect control mechanisms used by managers to control worker behaviour in a way that results in working conditions that are a form of modern slavery.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…This represents worker exploitation, which is a characteristic of modern slavery (Parker and Chung, 2018). In addition, reports surface from time to time of factory suicides and physical abuse of workers by managers and supervisors, which is also consistent with a form of modern slavery (Stevenson and Cole, 2018;Christ et al, 2019;Landman and Silverman, 2019;Mende, 2019;Pinheiro et al, 2019;Voss et al, 2019;Flynn and Walker, 2020). This paper examines 'how' power/distance and uncertainty avoidance aspects of Chinese culture affect control mechanisms used by managers to control worker behaviour in a way that results in working conditions that are a form of modern slavery.…”
Section: Discussionmentioning
confidence: 74%
“…The interviews discussed above highlight working conditions that are consistent with modern slavery (Stevenson and Cole, 2018;Christ et al, 2019;Landman and Silverman, 2019;Mende, 2019;Pinheiro et al, 2019;Voss et al, 2019;Flynn and Walker, 2020): workers are expected to work long hours without overtime pay, they can be unfairly dismissed, and they must give gifts to their managers in order to keep their jobs. In some cases, managers impose fines and physically punish workers they are displeased with.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We were specifically interested in how these supply chains across different legal systems are structured and governed, and how that impacts the risk of modern slavery. We found that the laws and regulations governing these supply chains often only address individual parts or tasks in the supply chain and are not aligned with the connected logic of an end-to-end supply chain (Pinheiro, Emberson, & Trautrims, 2019). Particularly in the case of beef, the supply chain becomes highly fragmented and -in the current business model -untraceable at the stages prior to the point when cattle are being sold to the large globally-operating beef processors.…”
Section: Effective Responses To Modern Slavery Require Changes In Intmentioning
confidence: 96%